Peran Keluarga dan Organisasi Remaja Masjid Dalam Dakwah Terhadap Remaja - Nahed Nuwairah, S.Ag., MH.I (UIN Antasari Banjarmasin, 2015)
The Problems of da’wah among adolescents in line with the increasing variety of juvenile delinquency is one of the da’wah agenda that must be addressed with a good strategy. In the perspective of da’wah, should be considered seriously juvenile characteristics in accordance with the situation and their condition. This paper discusses the strategy of da’wah that can be applied to teenagers through the optimization of the role of the family as the main foundation for the personality of adolescents and increase the role of youth organizations mosque as an alternative to efforts to